1990
DOI: 10.1055/s-2007-999459
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Fat Emulsions in Very Low Birthweight Neonates: Effect of Birthweight on Plasma Lipid Concentrations

Abstract: Plasma concentrations of various lipid fractions (total lipids, free glycerol, true triglycerides, free fatty acids, and cholesterol) were studied in 20 normally grown neonates ranging in birthweight from 820 to 1500 gm and in gestational age from 28 to 34 weeks. They were subdivided into three weight categories: 750 to 999, 1000 to 1249, and 1250 to 1500 gm. A lipid emulsion was infused at a constant rate over 24 hours, beginning with an hourly infusion rate of 0.04 gm/kg and increasing each day by 0.04 gm/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 7 publications
0
19
0
2
Order By: Relevance
“…In in vitro human immune cell models, olive-oilbased emulsions have also been shown not to alter lymphocyte proliferation or interleukin (IL)-2 release [12] to preserve neutrophil activation and functions [5,38] and to induce low tumor necrosis factor alpha and IL1b inhibition in mononuclear leucocytes when compared with soyabean-oil-based IVLE [30]. Preterm infants have very limited endogenous lipid stores [4]. IVLE are an attractive source of nutrition early in postnatal life because of their high energy density [39]; IVLE also enables the delivery of fat-soluble vitamins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In in vitro human immune cell models, olive-oilbased emulsions have also been shown not to alter lymphocyte proliferation or interleukin (IL)-2 release [12] to preserve neutrophil activation and functions [5,38] and to induce low tumor necrosis factor alpha and IL1b inhibition in mononuclear leucocytes when compared with soyabean-oil-based IVLE [30]. Preterm infants have very limited endogenous lipid stores [4]. IVLE are an attractive source of nutrition early in postnatal life because of their high energy density [39]; IVLE also enables the delivery of fat-soluble vitamins.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated reduced lipid clearance [1,26,27], while others found no association between hypertriglyceridemia and infection [17,34]. Tolerance of IVLE in the newborn is found to be inversely related to maturity and birth weight, with the more immature and smaller neonates at greatest risk for hypertriglyceridemia [4]. Premature infants have limited lipoprotein lipase concentrations that may hinder their ability to clear plasma lipids following IVLE infusion [33].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of plasma lip ids were repeated every 2 weeks until the infant's dis charge from the hospital or death. Concentrations of triglycerides were measured enzymatically with a com mercial kit (Triglyceride kit, fully enzymatic, Boehringer Mannheim Diagnostics, Indianapolis, Ind., USA) modified for 10-pl samples; a four-point glycerol stan dard curve was determined with each run of assays [18]. Concentrations of total cholesterol were deter mined enzymatically with a commercial kit (Enzy matic Cholesterol Kit, Stanbio Laboratory Inc., San Antonio, Tex., USA) modified for 5-pl samples; a fourpoint cholesterol standard curve (Preciset, Bochringer Mannheim Diagnostics) was determined with each run of assays.…”
Section: Methodsmentioning
confidence: 99%
“…In preterm and small-for-gestational-age newborns, intravenous fat elevates the concentrations of triglyce-rides and free fatty acids significantly more than in fullterm neonates, children, or adults [18,19]. These findings prompted us to determine blood viscosity and its determinants (hematocrit, plasma viscosity, and RBC aggregation and deformabililty) as well as vascular hindrance in preterm newborns, fullterm neonates, and children before and after IL infusion.…”
Section: Introductionmentioning
confidence: 99%